Q: What is 10x (6 11x) 6 property?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Isolate the variable. Get it by itself. 9+11x=89+x 9+11x-1x=89+x-1x Subtraction property of equality 9+10x=89 9+10x-9=89-9 subtraction property of equality 10x=80 x=8 division property of equality.

-x-6-(-11x) + (-1) Remove the brackets: -x-6+11x-1 Collect and simplify like terms: 10x-7 A - - is equal to a +

6-x+12 = 10x+7 6+12-7 = 10x+x 11 = 11x x = 1

10x-7+x+7 = 11x

Add -x -6y. Just like with numbers, subtract the first from the second to find what to add to the first to get the second; keeping like terms together: (10x - 4y) - (11x + 2y) = (10x - 11x) + (-4y - 2y) = (10 - 11)x + (-4 - 2)y = -x - 6y

Related questions

21

Isolate the variable. Get it by itself. 9+11x=89+x 9+11x-1x=89+x-1x Subtraction property of equality 9+10x=89 9+10x-9=89-9 subtraction property of equality 10x=80 x=8 division property of equality.

11x = 10x-19 Subtact 10x fromboth sides:- x = -19

The equivalent expression of 10x-11x is -x, or negative x.

21

-11x-1 = -10x-8 -11x+10 = -8+1 -1x = -7 x = 7

-x-6-(-11x) + (-1) Remove the brackets: -x-6+11x-1 Collect and simplify like terms: 10x-7 A - - is equal to a +

6-x+12 = 10x+7 6+12-7 = 10x+x 11 = 11x x = 1

-10x = x-33 -10x-x = -33 -11x = -33 x = 11

10x-7+x+7 = 11x

6 + 11x - 60 =6 - 60 + 11x = -54 + 11x = 11x -54

Add -x -6y. Just like with numbers, subtract the first from the second to find what to add to the first to get the second; keeping like terms together: (10x - 4y) - (11x + 2y) = (10x - 11x) + (-4y - 2y) = (10 - 11)x + (-4 - 2)y = -x - 6y